Populism and economic policy: lessons from Central and Eastern Europe. Issue 2 (17th February 2022) - Feldmann, Magnus; Popa, Mircea
ABSTRACT: A growing literature has identified a coherent economic model associated with populist governments in Central and Eastern Europe. This model runs counter to some aspects of the former neoliberal consensus in the region and to established theories of good governance. Considering three cases which are representative of these developments – Poland (since 2015), Hungary (since 2010), and Romania (2016–19) – we argue that a major unexplained puzzle is the relatively good economic performance of such governments. We develop three interrelated explanations for this apparent puzzle and test them using quantitative data. First, macroeconomic data show that the populist rhetoric of these parties is not associated with classical macroeconomic populism. Second, government accounting data show that public spending has been targeted towards specific groups and has not led to increasing tax burdens. Third, firm-level data on business confidence and institutional perceptions show no obvious negative effects associated with these governments.